Mesonephric-Like Adenocarcinoma of the Endometrium: Review of the Literature and Practical Diagnostic Recommendations. Issue 5 (September 2022) - Chapel, David B.; Park, Kay J.
Abstract: Mesonephric-like adenocarcinomas are endometrial and ovarian neoplasms of müllerian origin with morphologic, immunophenotypic, and molecular evidence of mesonephric-type transdifferentiation, as well as considerable homology with endometrioid tumors. First described in 2016, mesonephric-like adenocarcinomas are morphologically indistinguishable from "true" mesonephric adenocarcinomas of the uterine cervix, but the latter are distinguished by (1) primary localization to the cervical wall, (2) frequent association with mesonephric remnants, and (3) in some cases, lack of mucosal involvement. Despite an overall low-grade morphology, mesonephric-like adenocarcinoma follows an aggressive clinical course, characterized by frequent and early recurrences, most often in the lung. Accordingly, accurate distinction of mesonephric-like adenocarcinoma from morphologic mimics—especially low-grade endometrioid adenocarcinoma—is critical. However, available evidence indicates that endometrial mesonephric-like adenocarcinomas are significantly underdiagnosed, likely due to their relative novelty, rarity, and considerable overlap with endometrioid neoplasia. Prospective recognition of characteristic morphologic features, a low threshold for application of diagnostic immunohistochemistry, and judicious use of molecular studies will permit accurate diagnosis in almost all cases.